2016
DOI: 10.1165/rcmb.2015-0108oc
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Engagement Mediates Prolyl Endopeptidase Release from Airway Epithelia via Exosomes

Abstract: Proteases are important regulators of pulmonary remodeling and airway inflammation. Recently, we have characterized the enzyme prolyl endopeptidase (PE), a serine peptidase, as a critical protease in the generation of the neutrophil chemoattractant tripeptide Pro-Gly-Pro (PGP) from collagen. However, PE has been characterized as a cytosolic enzyme, and the mechanism mediating PE release extracellularly remains unknown. We examined the role of exosomes derived from airway epithelia as a mechanism for PE release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 44 publications
(45 reference statements)
3
51
0
Order By: Relevance
“…We hypothesized that the PD‐L1 induction by TGFβ (Figures and ) might be similarly expressed in EVs as they represent mediators of intercellular communication under both physiological and disease conditions . In that the contribution of EVs to chronic lung disease and the role of serum‐derived EVs as potential biomarkers has been recently reported, studies were undertaken to determine whether the expression of PD‐L1 following fibroblast treatment with TGFβ could function in an analogous paracrine manner to mediate T cell anergy and/or fibroblast activation. This was addressed in Figure where (i) it was first shown that fibroblast‐derived EVs contained increased amounts of PD‐L1 after TGFβ stimulation; and (ii) the secreted EVs decreased T cell proliferation and increased fibroblast migration in a PD‐L1 dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the PD‐L1 induction by TGFβ (Figures and ) might be similarly expressed in EVs as they represent mediators of intercellular communication under both physiological and disease conditions . In that the contribution of EVs to chronic lung disease and the role of serum‐derived EVs as potential biomarkers has been recently reported, studies were undertaken to determine whether the expression of PD‐L1 following fibroblast treatment with TGFβ could function in an analogous paracrine manner to mediate T cell anergy and/or fibroblast activation. This was addressed in Figure where (i) it was first shown that fibroblast‐derived EVs contained increased amounts of PD‐L1 after TGFβ stimulation; and (ii) the secreted EVs decreased T cell proliferation and increased fibroblast migration in a PD‐L1 dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…ing protein for structural and immune cells, but is now considered the rate-limiting enzyme for free PGP formation and is released from airway epithelia via an exosomal pathway during inflammation (45). PGP-induced signaling is considered a feed-forward inflammatory signal wherein CXCR1 and CXCR2 ligation triggers neutrophil influx, driving the release of collagenase MMP9 from neutrophil tertiary granules, which cleaves more collagen and results in the release of additional PGP and subsequent neutrophil influx (46) (Figure 1).…”
Section: Collagen-derived Matrikinesmentioning
confidence: 99%
“…It was reported that PREP is released from airway epithelial cells through exosomes. The sputum of patients with cystic fibrosis colonized with Pseudomonas aeruginosa showed more exosomes and increased PREP protein expression (121).…”
Section: Copd Cystic Fibrosis and Idiopathic Pulmonary Fibrosis (Ipf)mentioning
confidence: 94%
“…PREP activity has been measured in sputum with Z-Gly-Pro-pNA and was 5 times higher in patients with cystic fibrosis compared to healthy controls (93). PREP mRNA, protein expression and enzymatic activity has been shown in multiple airway epithelial cells, both in cell lines and primary cells (121). PREP could be found in the medium of cystic fibrosis bronchial epithelial cells and was increased after stimulation with lipopolysaccharide (LPS), without an increase in PREP mRNA.…”
Section: Copd Cystic Fibrosis and Idiopathic Pulmonary Fibrosis (Ipf)mentioning
confidence: 99%